Paremies as a meams of political impact on an addressee in publicistic discourse of Mihayilo Grushevskyi (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article is devoted to functional features and communicative-pragmatic potential of proverbs and proverbial phrases in the publistical inheritance of Mykhailo Hrushevsky. The analysis of communicative influence and modificated paremies on the consciousness of receptionist is made in the article.
Keywords: paremial units; functional peculiarities; pragmatical meaning; individual author’s transformation